Antibiofilm effects of titanium surfaces modified by laser texturing and hot-pressing sintering with silver - Gonçalves, Inês M. R. (2021)
Peri-implant diseases are one of the main causes of dental implant failure. New strategies for dental implants manufacturing have been developed to prevent the accumulation of bacteria and related inflammatory reactions. The main aim of this work was to develop laser-treated titanium surfaces covered with silver that generate a electrical dipole to inhibit the oral bacteria accumulation. Two approaches were developed for that purpose. In one approach a pattern of different titanium dioxide thickness was produced on the titanium surface, using a Q-Switched Nd:YAG laser system operating at 1064 nm. The second approach was to incorporate silver particles on a laser textured titanium surface. The incorporation of the silver was performed by laser sintering and hot-pressing approaches. The anti-biofilm effect of the discs were tested against biofilms involving 14 different bacterial strains growth for 24 and 72 hr. The morphological aspects of the surfaces were evaluated by optical and field emission guns scanning electronical microscopy (FEGSEM) and therefore the wettability and roughness were also assessed. Physicochemical analyses revealed that the test surfaces were hydrophilic and moderately rough. The oxidized titanium surfaces showed no signs of antibacterial effects when compared to polished discs. However, the discs with silver revealed a decrease of accumulation of Porphyromonas gingivalis and Prevotella intermedia strains. Thus, the combination of Nd:YAG laser irradiation and hot-pressing was effective to produce silver-based patterns on titanium surfaces to inhibit the growth of pathogenic bacterial species. The laser parameters can be optimized to achieve different patterns, roughness, and thickness of the modified titanium layer regarding the type and region of the implant.